Cricket Achievement Management Pattern In Muaro Jambi Regency - Fitra Fitra; Palmizal A; Bangkit Yudho Prabowo (Jurnal Pendidikan Jasmani (JPJ), 2026)
Cricket is a team sport that pits two teams against each other, each consisting of eleven players. The game uses a ball and a bat, with the main objective being to score points called runs. The performance development pattern is a strategic plan or system that is structured in an orderly, continuous, and focused manner to develop athletes' talents from an early age so that they can achieve their best performance at the regional, national, and international levels. It is hoped that the results of this study can make a positive contribution as a reference in the formulation of a more focused, systematic, and sustainable cricket development strategy in Muaro Jambi Regency. This type of research is quantitative descriptive using a questionnaire method. The research sample used total sampling technique, consisting of 22 people. Of all respondents, 13 people (59%) were categorized as Very Good, while 9 respondents (41%) were categorized as Good. Among male athletes, most respondents were in the Excellent category, namely 8 out of 11 people (73%), while 3 respondents (27%) were in the Good category. Among female athletes, 55% were categorized as Good, while the remaining 45% were categorized as Very Good.